Patient's Safety in Your Hands - Habip GEDİK; Timothy A. VOSS; Andreas VOSS (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2013)
Hand hygiene is a general term describing any hand cleansing (and care) action. Hand cleansing with soap and water has been the primary measure of personal hygiene for centuries. In the 20th century, many studies revealed the important role of healthcare workers’ hands in the transmission of nosocomial pathogens. This leads to the first national hand hygiene guidelines being published in the 1980s. Alcohol-based hand antiseptics include ethanol, isopropanol or n-propanol, or a combination of two of those products. Addition of chlorhexidine, quaternary ammonium compounds, octenidine or triclosan to alcohol-based formulations can result in persistent activity. Perceived barriers to adherence with hand hygiene practice recommendations include skin irritation caused by hand hygiene agents, inaccessible hand hygiene supplies, interference with healthcare worker patient relationships, patient needs perceived as a priority over hand hygiene, wearing og gloves, forgetfulness, lack of knowledge of guidelines, insufficient time for hand hygiene, high workload and understaffing, and the lack of scientific information showing a definitive impact of improved hand hygiene on healthcare associated infections rates.